Effectiveness of Mindfulness-Based Cognitive Counseling Integrated with Construal Level Theory for University Students’ Mental Health - Febrianti, Thrisia; Tyas Asih, Marlia (Universitas Negeri Padang, 2025)
Mental health problems among university students, notably stress, anxiety, and depression, continue to increase, negatively impacting psychological functioning and academic performance. This study evaluated the effectiveness of an integrated Mindfulness-Based Cognitive Counseling (MBCC) and Construal Level Theory (CLT) intervention in improving students‘ mental health. A quasi-experimental pretest-posttest design with a control group was employed, with 24 participants (12 intervention, 12 control) selected via purposive sampling. Instruments included DASS-21, the Five-Facet Mindfulness Questionnaire, and a CLT-based psychological distance scale. MANOVA results showed a significant multivariate effect of the intervention (Wilks’ Λ = .68; F(3, 21) = 3.28; p = .041; η2 = .32). Univariate analyses indicated significant reductions in psychological distress (p = .005), and significant increases in mindfulness (p = .002) and psychological distance (p = 0.023). These findings suggest that the integrated MBCC-CLT intervention is effective in enhancing mental health among university students by reducing distress and promoting adaptive awareness and cognitive appraisal.